A laboratory study of spontaneous platelet aggregation. Issue 4 (May 1971) - Friedlander, I.; Cook, I. J. Y.; Hawkey, C.; Symons, C.
Abstract : During studies on platelet aggregation using the EEL platelet aggregation meter, 8% of the individuals tested were found to have platelets which aggregated spontaneously when citrated, platelet-rich plasma was stirred at 37°C. The EEL aggregation meter differs from other machines in that it incorporates a vertical stirrer which subjects platelets to greater mechanical force. When using this machine it is suggested that spontaneous platelet aggregation is related to increased mechanical fragility of the platelets and low levels of plasma ADP-inhibitor.